A Methods engineering study on JY Ceramics - Barro, Jesselyn B.; Chu, Ma. Rosario B.; Claridad, Ma. Lourdes Bernadette V. (Diliman, Quezon City College of Engineering, 1999)
JY Ceramics, a manufacturer of varied lines of balusters, is a small but rapidly progressing company. Its manufacturing plant is located at Angono, Rizal but its main office is found in Cubao, Quezon City. This Work Study's main goal is to rectify the present system of the said company by proposing improvements on working conditions, plant lay-out and methods of production. This study follows textbook Work Study methodology to achieve these goals. The production of balusters is composed of several processes, namely, mixing, casting, sponging, drying, glazing and firing. Due to time constraint, the bulk of the study is focused upon the casting process for this is where the main problems in production lie. The company uses 2 casting methods -- manual casting and filter press casting. The three main problems in casting include bottlenecks between the filter press casting and inspection, poorer quality of balusters in manual casting and lengthy manual casting. The company also have a problem on the present lay-out. The lay-out is quite disorganized and messy. Data regarding the production of balusters and the company operations, in general, are gathered through numerous plant visits and interviews of key personnel. The different processes involved in the production-mixing, casting, drying, sponging, glazing and firing--are individually documented. Also, the general working conditions, plant lay-out, company background, general systems and procedures are all property documented with data. Using the data gathered, production problems were determined by cause and effect relationships and appropriate charts, in an attempt to identify and isolate the root problem and recognize its limiting factors. Alternatives are formulated and presented with their corresponding pros and cons to come up with solutions to the problems. Eventually, only one among the alternatives is chosen and is followed by recommendations. The group suggests that inspectors must be added to eliminate the bottleneck between casting and inspection. To improve the quality of balusters produced in manual casting, the best solution is to constantly train the workers. And lastly, manual casting must be eliminated to shorten the production time. The group also suggests that the company adapt a computerized system of keeping company records. A proposed lay-out is also presented, which exhibits the most efficient material and process flow for plant operations.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Systems analysis